2022
DOI: 10.1155/2022/7172583
|View full text |Cite
|
Sign up to set email alerts
|

miR-99a-5p: A Potential New Therapy for Atherosclerosis by Targeting mTOR and Then Inhibiting NLRP3 Inflammasome Activation and Promoting Macrophage Autophagy

Abstract: Objective. MicroRNAs have been revealed to be involved in the development of atherosclerosis. The present study is aimed at exploring the potential of miR-99a-5p as a therapy for atherosclerosis. We suspected that miR-99a-5p might inhibit NLRP3 inflammasome activation and promote macrophage autophagy via constraining mTOR, therefore, alleviating atherosclerosis. Methods. The cell viability in ox-LDL-induced THP-1 macrophages was assessed by CCK-8 assay. Bioinformatic analysis was used to predict the target gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Deficiency in hsa-miR-21-5p leads to increased recruitment of CD11b+ monocytes/macrophages and an increased inflammatory response [ 50 , 51 ]. Both hsa-miR-99a-5p and miR-574-5p inhibit NLRP3 inflammasome by promoting macrophage autophagy through downregulation of mTOR signaling and by suppressing leukocytes infiltration and downregulating NF-κB [ 52 , 53 ]. Also, miR-107 protects against inflammation and apoptosis of endothelial cells via KRT1-dependent Notch signaling pathway [ 54 ] whereas hsa-let-7b-5p regulates neutrophil function and reduces neutrophilic inflammation by suppressing the canonical TLR4/NF-κB pathway [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency in hsa-miR-21-5p leads to increased recruitment of CD11b+ monocytes/macrophages and an increased inflammatory response [ 50 , 51 ]. Both hsa-miR-99a-5p and miR-574-5p inhibit NLRP3 inflammasome by promoting macrophage autophagy through downregulation of mTOR signaling and by suppressing leukocytes infiltration and downregulating NF-κB [ 52 , 53 ]. Also, miR-107 protects against inflammation and apoptosis of endothelial cells via KRT1-dependent Notch signaling pathway [ 54 ] whereas hsa-let-7b-5p regulates neutrophil function and reduces neutrophilic inflammation by suppressing the canonical TLR4/NF-κB pathway [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…By targeting the homeobox A1 gene, miR-99a-5p acted as an atherosclerosis inhibitor, reducing lesion formation. Recent research showed selective miR-99a-5p overexpression significantly decreased atherosclerotic lesions and lowered NLRP3 inflammatory protein expression [ 26 ], leading to reduced inflammasome complex and inflammatory cytokine levels. Overall, these significant miRNAs, including miR-101-3p, miR-140-3p, and miR-99a-5p, hold clinical utility for the early prediction of obesity-related myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the modulation of microRNAs could be crucial in the regulation of macrophage autophagy. Wang et al, in a study on ox-LDL-induced THP-1 macrophages, found that miR-99a-5p overexpression inhibited NACHT, LRR, and PYD domains-containing protein 3 (NLRP3) inflammasome activation and stimulated macrophage autophagy through mTOR, producing a lower atherosclerotic lesion burden [49]. Shao et al treated apoE −/− mice and RAW264.7 cells with miR-29a mimic, and found polarization of macrophages toward an M2 phenotype, along with overexpression of autophagy-related proteins [50].…”
Section: Targeting Macrophages For Atherosclerosis Treatmentmentioning
confidence: 99%